Cathodal tDCS and robotic therapy for upper limb rehabilitation in chronic stroke: a randomized controlled trial - Chen, Jin; Du, Jingang; Wang, Chunfang; Yu, Hongli (Frontiers in Neurology, 2025)
IntroductionThis randomized controlled trial evaluated the effect of contralesional cathodal transcranial direct current stimulation (ctDCS) combined with robotic therapy (RT) on upper limb recovery in patients with chronic subcortical ischemic stroke.MethodsThirty-one participants were randomized to receive either active ctDCS or sham stimulation during RT, administered five times per week for four weeks. Outcomes were assessed using clinical rehabilitation scales and robotic evaluation of movement parameters at baseline, immediately post-intervention, and at two-week follow-up.ResultsThe active group demonstrated significantly greater improvement in Upper Extremity Fugl-Meyer Assessment, with a between-group difference of 4.61 (95% CI: 51.36 to 55.46, p = 0.023) post-intervention. Functional efficiency (mean difference: 1.82, 95% CI: 9.13 to 12.00) and movement speed (mean difference: 3.46, 95% CI: 51.60 to 56.74) also favored the active group.ConclusionThese findings suggest that combining ctDCS with RT may enhance the efficiency of specific upper limb motor tasks in patients with chronic subcortical ischemic stroke, compared to RT alone.